2003
DOI: 10.1038/sj.jp.7210986
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Outpatient Regimens in the Management of Nausea and Vomiting in Pregnancy

Abstract: Objective:This study compares pyridoxine-metoclopramide combination therapy to prochlorperazine and promethazine monotherapies in the outpatient treatment of nausea and vomiting in pregnancy. Study Design:In total, 174 first trimester, singleton pregnancies were evaluated for nausea and vomiting. Patients were prospectively randomized into three treatment groups: pyridoxine-metoclopramide, prochlorperazine, or promethazine. Prior to, and on the third day, patients recorded their subjective responses to the giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 17 publications
0
39
0
1
Order By: Relevance
“…A randomized control study of 75 patients hospitalized for hyperemesis gravidarum did not demonstrate a difference in effectiveness between intravenous treatment with 25 mg promethazine or 10 mg metoclopramide every 8 h for 24 h [43]. As an initial therapeutic agent, a study of promethazine versus metoclopramide in combination with pyroxamine showed that the later treatment resulted in higher rates of reported improvement as stated by patients [44]. Promethazine has been shown to cross the placental barrier and be expressed in breast milk.…”
Section: Promethazinementioning
confidence: 99%
“…A randomized control study of 75 patients hospitalized for hyperemesis gravidarum did not demonstrate a difference in effectiveness between intravenous treatment with 25 mg promethazine or 10 mg metoclopramide every 8 h for 24 h [43]. As an initial therapeutic agent, a study of promethazine versus metoclopramide in combination with pyroxamine showed that the later treatment resulted in higher rates of reported improvement as stated by patients [44]. Promethazine has been shown to cross the placental barrier and be expressed in breast milk.…”
Section: Promethazinementioning
confidence: 99%
“…These findings do not lend any support to pyridoxine effectiveness in HG when used in conjunction with metoclopramide. A recent study with 3 outpatient treatment arms, comparing pyridoxine-metoclopramide, prochlorperazine or promethazine for NVP, has shown pyridoxine-metoclopramide therapy to be superior, but the study design did not allow for the separate effect of pyridoxine to be assessed [16] .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear data as to the most appropriate drug if these are ineffective. In a study of 174 singleton pregnancies with nausea and vomiting, combined therapy with pyridoxine and metoclopramide was found to be superior to monotherapy with either promethazine or prochlormethazine [61].…”
Section: Treatmentmentioning
confidence: 98%